Perioperative Systemic Inflammation in Lung Cancer Surgery - Furák, József; Németh, Tibor; Lantos, Judit; Fabó, Csongor; Géczi, Tibor; Zombori-Tóth, Noémi; Paróczai, Dóra; Szántó, Zalán; Szabó, Zsolt (Frontiers in Surgery, 2022)
Systemic inflammation (SI) is a response of the immune system to infectious or non-infectious injuries that defends the body homeostasis. Every surgical intervention triggers SI, the level of which depends on the extent of damage caused by the surgery. During the first few hours after the damage, the innate or natural immunity, involving neutrophils, macrophages, and natural killer cells, plays a main role in the defense mechanism, but thereafter the adaptive immune response ensues. The number of leukocytes is elevated, the levels of lymphocytes and natural killer cells are reduced, and the cytokines released after surgery correlate with surgical damage. Minimally invasive thoracic surgery procedures induce less inflammatory response and reduce the immune defense in patients to a more moderate level compared with the open surgery procedures; this immunosuppression can be further diminished in spontaneous ventilation cases. The normal functioning of the immune defense is important in controlling the perioperative circulatory tumor cells. Moreover, elevated levels of inflammatory cytokines before immune therapy have a negative impact on the response, and significantly shorten the progression-free survival. Clinically, the lower are the levels of cytokines released during lung surgery, the lesser is the postoperative morbidity, especially pneumonia and wound infection. The return to normal levels of lymphocytes and cytokines occurs faster after spontaneous ventilation surgery. The use of locoregional anesthesia can also reduce SI. Herein, we review the current knowledge on the effects of different operative factors on postoperative SI and defense mechanism in lung cancer surgery.